A CRITICAL SOCIOLINGUISTIC APPROACH TO THE ANALYSIS OF POLITICAL DIALECT DIFFERENCES - Haider Saad Yahya Jubran (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The current paper is intended to examine political dialect variations critically. It foreshadows that the language that politicians use pre-presidentially is different from the language they use thereafter. Variation and changeability can best be studied within the agenda of critical sociolinguistics which has established a connection between people's place in the societal hierarchy and the linguistic and other phenomena of oppressions in that place. Accordingly. Twenty political English and Arabic discourses are analyzed socio-critically.